Overtraining and immune system: a prospective longitudinal study in endurance athletes - Gabriel, H. H.; Urhausen, A.; Valet, G.; Heidelbach, U.; Kindermann, W. (Medicine & Science in Sports & Exercise, 1998)
It is concluded that OT (overtraining) does not lead to clinically relevant alterations of immunophenotypes in peripheral blood and especially that an immunosuppressive effect cannot be detected. Immunophenotyping may provide help with the diagnosis of OT in future, but the diagnostic approach presented here requires improvements before use in sportsmedical practice is enabled.